1992
DOI: 10.2307/1131348
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Maternal Practices and Characteristics to Children's Vicarious Emotional Responsiveness

Abstract: This study examined the relations of maternal vicarious emotional responding and child-rearing practices, as well as familial emotional environment, to 5-6 and 8-9-year-old children's vicarious emotional responding. There were some correspondences between mothers' and children's heart rate, facial, and self-reported reactions to a sympathy-inducing film. Maternal sympathy/perspective taking and reinforcement of sympathy/prosocial behavior, as well as negative subordinate emotion in the home, were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 21 publications
9
101
1
3
Order By: Relevance
“…This finding is consistent with those of other studies that indicate that female adolescents are more susceptible to the influence of family emotional climate than male adolescents are (e.g.. Eisenberg et al, 1992;Jaycox & Repetti, 1993). Because the gender differences in this study were not very pronounced and were limited to the area of general psychological health, further clarification is needed.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with those of other studies that indicate that female adolescents are more susceptible to the influence of family emotional climate than male adolescents are (e.g.. Eisenberg et al, 1992;Jaycox & Repetti, 1993). Because the gender differences in this study were not very pronounced and were limited to the area of general psychological health, further clarification is needed.…”
Section: Discussionsupporting
confidence: 92%
“…Test-retest reliability is high (Halberstadt, Cassidy, Stifter, Parke, & Fox, 1995) and good internal consistency of the subscales has been demonstrated (Cassidy et al, 1992;Eisenberg et al, 1992). Cronbach's alphas for the present study were .91 for positive emotion, .60 for negative dominant emotion, and .65 for negative submissive emotion.…”
Section: Maternal Measuressupporting
confidence: 53%
“…In contrast, insecure attachment to parents predisposes adolescents to become self-focused and more likely to experience personal distress when observing others in need. Self-focus and personal distress have been associated inversely with empathy and concern for others (Carlson & Miller, 1987;Eisenberg et al, 1992). The less attachment security adolescents experience, the less likely they are to act affectionately or show concern.…”
Section: Discussionmentioning
confidence: 99%
“…Carlson and Miller (1987) proposed that when such events occur, prosocial responsiveness is less likely to occur. In addition, the experience of negative affectivity induces a state of personal distress in the adolescent that also can inhibit prosocial activity (Eisenberg et al, 1992). Carlo, Roesch, and Melby (1998) found that anger was related inversely to adolescents' prosocial behavior and felt sympathy.…”
mentioning
confidence: 99%